Understanding Practicing and Assessment of 21st-century Skills for Learners in Makerspaces and Fablabs - Ioannou, Andri; Miliou, Ourania; Timotheou, Stella; Kitsis, Andreas; Adamou, Maria; Mavri, Aekaterini (My University, 2024)
Despite the opportunities that makerspaces and FabLabs offer for the development of 21st-century skills, understanding how these skills are being practiced and assessed in these spaces has been proven challenging. In this work, we address this gap through an interview study investigating 13 maker-educators’ practices across different makerspaces and FabLabs. The findings reveal that, in general, maker-educators’ practice is not guided by any formal 21st century skills framework. Instead, they draw ideas from their national school curricula, literature, and primarily their own experiences and perceived best practices in their contexts. They report evidence of practicing 21st-century skills, most frequently referring to five skills: collaboration, creativity, communication, life/social skills, and problem-solving. Yet, they do not explicitly assess the development of these skills, for reasons that have to do with (i) the practical nature of making, which emphasizes the development of a tangible result and not skills development as such, (ii) the demanding nature of the making activities, which requires a lot of hands-on time, leaving no room for assessment, (iii) the making ethos, which presents maker-educators with choices around what to pursue and how to go about it, and cannot restrict making activities within the boundaries of formal assessment practices. The study helped to document some making practices linked to the practicing of 21st-century skills, as reported by the participating maker-educators. Future work could focus on the design of assessment practices and tools that can help to capture and advance the development of 21st-century skills in maker contexts, while respecting the openness in the making ethos.
Keywords: 21st -century skills; Assessment; Makerspaces; FabLabs; Maker education